Missense variant c.1460 T > C (p.L487P) enhances protein degradation of ER mannosyltransferase ALG9 in two new ALG9-CDG patients presenting with West syndrome and review of the literature - Himmelreich, Nastassja; Dimitrov, Bianca; Zielonka, Matthias; Hüllen, Andreas; Hoffmann, Georg F.; Juenger, Hendrik; Müller, Herbert; Lorenz, Imke; Busse, Birgit; Marschall, Christoph; Schlüter, Gregor; Thiel, Christian (Molecular genetics and metabolism, 2022)
ALG9-CDG is a CDG-I defect within the group of Congenital Disorders of Glycosylation (CDG). We here describe the clinical symptoms of two new and unrelated ALG9-CDG patients, both carrying the novel homozygous missense variant c.1460 T > C (p.L487P) in the ALG9 gene which led to global developmental delay, psychomotor disability, facial dysmorphisms, brain and heart defects, hearing loss, hypotonia, as well as feeding problems. New clinical symptoms comprised West syndrome with hypsarrhythmia. Quantitative RT-PCR analysis revealed a significantly enhanced ALG9 mRNA transcript level, whereas the protein amount in fibroblasts was significantly reduced. This could be ascribed to a stronger degradation of the mutated ALG9 protein in patient fibroblasts. Lipid-linked oligosaccharide analysis showed an ALG9-CDG characteristic accumulation of Man6GlcNAc2-PP-dolichol and Man8GlcNAc2-PP-dolichol in patient cells. The clinical findings of our patients and of all previously published ALG9-CDG patients are brought together to further expand the knowledge about this rare N-glycosylation disorder. SYNOPSIS: Homozygosity for p.L487P in ALG9 causes protein degradation and leads to West syndrome.
Gesehen am 28.08.2022